2017
DOI: 10.5194/tc-11-2595-2017
|View full text |Cite
|
Sign up to set email alerts
|

Basin-scale heterogeneity in Antarctic precipitation and its impact on surface mass variability

Abstract: Abstract. Annually averaged precipitation in the form of snow, the dominant term of the Antarctic Ice Sheet surface mass balance, displays large spatial and temporal variability. Here we present an analysis of spatial patterns of regional Antarctic precipitation variability and their impact on integrated Antarctic surface mass balance variability simulated as part of a preindustrial 1800-year global, fully coupled Community Earth System Model simulation. Correlation and composite analyses based on this output … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 44 publications
(66 reference statements)
2
53
0
Order By: Relevance
“…Additional features in the spatial pattern of precipitation change are associated with regional foci of ozone-depletion-forced atmospheric circulation changes. Most clearly, ozone depletion-driven Amundsen-Bellingshausen Sea Low strengthening (England et al, 2016) favors more/less frequent intrusions of moisture-loaded air over the eastern/western WAIS (Fyke et al, 2017), resulting in the prominent WAIS precipitation change dipole. Another foci of lower DJF pressure at ∼140 ∘ E promotes a snowfall response dipole in east/west Wilkes Land (East Antarctica Ice Sheet, EAIS), with the separation between the poles well represented by the north/south trending ice sheet divide at ∼135 ∘ E. Finally, a region of insignificant pressure change in the deep EAIS interior promotes two local minima in precipitation change westward of the Dome Argus and Dome Fuji ice divides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional features in the spatial pattern of precipitation change are associated with regional foci of ozone-depletion-forced atmospheric circulation changes. Most clearly, ozone depletion-driven Amundsen-Bellingshausen Sea Low strengthening (England et al, 2016) favors more/less frequent intrusions of moisture-loaded air over the eastern/western WAIS (Fyke et al, 2017), resulting in the prominent WAIS precipitation change dipole. Another foci of lower DJF pressure at ∼140 ∘ E promotes a snowfall response dipole in east/west Wilkes Land (East Antarctica Ice Sheet, EAIS), with the separation between the poles well represented by the north/south trending ice sheet divide at ∼135 ∘ E. Finally, a region of insignificant pressure change in the deep EAIS interior promotes two local minima in precipitation change westward of the Dome Argus and Dome Fuji ice divides.…”
Section: Resultsmentioning
confidence: 99%
“…Antarctic ice dynamics are not represented. Previous studies (Fyke et al, 2017;Lenaerts et al, 2016) have described a reasonable CESM representation of Antarctic precipitation spatial distribution, mean climatology, and natural variability relative to regional models and direct observations. This is confirmed by comparison of P − E (precipitation minus evaporation) between CESM and reconstructed values based on ice cores and the Modern-Era Retrospective analysis for Research and Applications, Version 2 (MERRA-2) atmospheric reanalysis (see section 2.2), shown in supporting information Figure S1.…”
Section: Climate Model Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rignot et al (2008) observed no significant mass changes in this region between 1992 and 2006 using the input-output method. Gardner et al (2018) compared present-day ice flow velocities to measurements from 2008. They obtain a slightly reduced ice discharge in DML (which would support the hypothesis of a dynamic thickening), while they observe a small increase in discharge for Enderby Land.…”
Section: Ice Sheet Mass Time Seriesmentioning
confidence: 99%
“…Although the mean (grounded) AIS SMB is almost six times higher than the GrIS SMB (~2,150 vs. ~365 Gt/year), its absolute interannual variability is actually smaller (~100 Gt/year, or ~5% of the mean). This can be explained by (1) only precipitation variability contributing to AIS SMB variability, in the general absence of surface runoff, and sublimation being about ten times smaller and with low interannual variability, and (2) a larger surface area of the AIS, where negative precipitation anomalies in some regions are compensated by positive anomalies elsewhere (Fyke et al, ).…”
Section: Temporal Variability and Trends In Ice Sheet Smbmentioning
confidence: 99%